2006
DOI: 10.1089/fpd.2006.3.222
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Significance of Antimicrobial-Resistant Gram-Negative Bacteria in Raw Bulk Tank Milk

Abstract: The dairy farm environment and animals on the farm serve as important reservoirs of pathogenic and commensal bacteria that could potentially gain access to milk in the bulk tank via several pathways. Pathogenic gram-negative bacteria can gain access to bulk tank milk from infected mammary glands, contaminated udders and milking machines, and/or from the dairy farm environment. Contaminated raw milk when consumed by humans or fed to animals on the farm can result in gastroenteric infections in humans and animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 59 publications
1
36
0
1
Order By: Relevance
“…The antibacterial activity of gallotannins has very recently been reported from Galla chinensis (Tian et al, 2009) and Mangifera indica L. (Engels et al, 2009), but their antibacterial activities, including anti-Gram-negative activity, have yet to be thoroughly elucidated. Antimicrobial-resistant Gramnegative bacteria, including foodborne pathogens, have become a worldwide concern in the food preservation and healthcare industries (Straley et al, 2006;White et al, 2004). Since the phytochemicals have been reported to harbour a more complex and diverse library of structures than synthetic chemicals, they are expected to constitute an alternative source of materials for the treatment of drug-resistant bacteria.…”
Section: Bacteriostatic Effects Of Component 1 Against Gram-positive mentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial activity of gallotannins has very recently been reported from Galla chinensis (Tian et al, 2009) and Mangifera indica L. (Engels et al, 2009), but their antibacterial activities, including anti-Gram-negative activity, have yet to be thoroughly elucidated. Antimicrobial-resistant Gramnegative bacteria, including foodborne pathogens, have become a worldwide concern in the food preservation and healthcare industries (Straley et al, 2006;White et al, 2004). Since the phytochemicals have been reported to harbour a more complex and diverse library of structures than synthetic chemicals, they are expected to constitute an alternative source of materials for the treatment of drug-resistant bacteria.…”
Section: Bacteriostatic Effects Of Component 1 Against Gram-positive mentioning
confidence: 99%
“…Antimicrobial-resistant foodborne pathogens can be transmitted to humans via the ingestion of contaminated foods of animal origin or contaminated water. In particular, zoonotic Gram-negative bacterial pathogens such as Campylobacter, E. coli, Salmonella, and Yersinia can result in intractable and severe disease (Straley et al, 2006;White, Zhao, Singh, & McDermott, 2004). Phytochemicals with complex and diverse structures, which are synthesised to protect the plant against pathogen invasion, might constitute valuable materials for the development of novel antimicrobials (Simoes, Bennett, & Rosa, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The picture became darker when came evidences that environmental microbiota present in antibiotic free environments showed to possess an as enormous and diverse number of AR genes as present in pathogenic microbiota (Aminov, 2009). Further evidences point to microorganisms associated with food, animals, and water as the main sources for resistance genes; commensals among them food commensals are also considered as a reservoir of AR (Knezevic & Petrovic, 2008;Straley et al, 2006), in fact according to Marshall et al (2009) a rather underappreciated reservoir of AR. In developed countries, several parameters define a raw milk of "good quality" when it is absent of drug or antibiotics residues, when the legal limit of somatic cells per millilitre of milk is below 4x10 5 /mL (excessive values may be indicating the presence of mastitis in the cow herd), when the bacteriological acceptance level is satisfied.…”
Section: Introductionmentioning
confidence: 99%
“…Strain 8.2 was not included in these tests, since its spectrum of action and the plasmidial DNA profile (data not shown) suggested that this strain was identical to strain 8.1. literature, resistance to antibiotics has become common amongst strains isolated from milk and dairy products (ARSLAN et al, 2011;BEENA et al, 2011). Straley et al (2006) verified that Pseudomonas spp. isolated from bulk tank milk samples were the dominant non-coliform Gram-negative bacteria and showed the highest levels of resistance to antibiotics.…”
Section: Susceptibility Of the Inhibitory Substances To Naohmentioning
confidence: 82%